Tectonic and sedimentary controls on widespread gas emissions in the Sea of Marmara: Results from systematic, shipborne multibeam echo sounder water column imaging. Issue 5 (18th May 2015) - Dupré, Stéphanie; Scalabrin, Carla; Grall, Céline; Augustin, Jean‐Marie; Henry, Pierre; Şengör, A. M. Celal; Görür, Naci; Çağatay, M. Namık; Géli, Louis
Abstract Understanding of the evolution of fluid‐fault interactions during earthquake cycles is a challenge that acoustic gas emission studies can contribute. A survey of the Sea of Marmara using a shipborne, multibeam echo sounder, with water column records, provided an accurate spatial distribution of offshore seeps. Gas emissions are spatially controlled by a combination of factors, including fault and fracture networks in connection to the Main Marmara Fault system and inherited faults, the nature and thickness of sediments (e.g., occurrence of impermeable or gas‐bearing sediments and landslides), and the connectivity between the seafloor and gas sources, particularly in relation to the Eocene Thrace Basin. The relationship between seepage and fault activity is not linear, as active faults do not necessarily conduct gas, and scarps corresponding to deactivated fault strands may continue to channel fluids. Within sedimentary basins, gas is not expelled at the seafloor unless faulting, deformation, or erosional processes affect the sediments. On topographic highs, gas flares occur along the main fault scarps but are also associated with sediment deformation. The occurrence of gas emissions appears to be correlated with the distribution of microseismicity. The relative absence of earthquake‐induced ground shaking along parts of the Istanbul‐Silivri and Princes Islands segments is likely the primary factor responsible for the comparative lack of gas emissions along these fault segments. The spatiotemporal distribution of gas seeps may thus provide a complementary way to constrain earthquake geohazards by focusing the study on some key fault segments, e.g., the northern part of the locked Princes Islands segment.